Moderation of parental socioeconomic status on the relationship between birth health and developmental coordination disorder at early years - Tran, Huynh-Truc; Tseng, Yu-Ting; Chen, Shuya; Wu, Sheng K.; Li, Yao-Chuen (Frontiers in Pediatrics, 2023)
Objective This study investigated whether parental SES moderates the effect of birth health on Developmental Coordination Disorder (DCD) in preschool children. Methods One hundred and twenty-two children aged 4 to 6 years were enrolled in the study. The Movement Assessment Battery for Children –2nd Edition (MABC-2) test was used to assess the motor coordination of children. They were preliminarily categorized into either the DCD (<=16th percentile, n = 23) or typically developing (TD) group (>16th percentile, n = 99) based on the testing results. All children in the DCD group were further confirmed to meet other diagnostic criteria of the DSM-V using the intellectual test and parental questionnaires. Moderation analysis was conducted using the PROCESS macro for SPSS, and 95% confidence intervals with a bootstrap procedure were calculated to identify the significant moderating effect. Results Maternal education (unstandardized coefficient = 0.6805, SE = 0.3371, p < 0.05) and maternal employment status (unstandardized coefficient = 0.6100, SE = 0.3059, p < 0.05) were found to moderate the relationship between birth length and the probability of having DCD. Moreover, the relationship between birth weight and the probability of having DCD was moderated by the annual household income (unstandardized coefficient = −0.0043, SE = 0.0022, p < 0.05). Conclusion The lower maternal education level and maternal unemployment strengthened the negative relationship between birth length and the probability of having DCD. Additionally, the negative relationship between birth weight and the probability of having DCD was statistically significant in high annual household salaries.